A Case Report on Mixed Epithelial and Stromal Tumor of the Kidney with Serous Cystadenoma Tumors of the Ovary - Silvia Taccogna; Martina D’Angelo; Sara Ienzi; Massimo Pezzatini; Andrea Liverani; Roberto D’Ascenzo; Francesco Angelini (New Frontiers in Medicine and Medical Research Vol. 10, 2021)
Mixed epithelial and stromal tumor (MEST) of the kidney is a rare tumor composed of epithelial and stromal cells. Steroid hormones seem to have a role in genesis and evolution of MESTs family, considering the marked female predominance, common history of long-term estrogen replacement, the frequent expression of estrogen (ER) and progesterone (PR) receptors in tumor mesenchymal component. We report the case of a 37-year-old woman admitted to the Department of Surgery because of abdominal pain. She had taken oral estrogen-progestin therapy for 4 years until the age of 35 for dysmenorrhea. During an abdominal ultrasound (US) was identified a left ovarian cyst, 60 mm x 20 mm, suggestive of simple cyst. Then a US repeated after 12 months showed the enlargement of the ovarian cyst (76 mm × 53 mm x 78 mm) and the appearance of a new exophytic cystic-solid mass of 120 mm in the lower pole of the left kidney. The patient underwent laparoscopic left partial nephrectomy and left ovariectomy. Histopathological examination and immunohistochemical analysis was consistent with a MEST of the kidney and a primary serous cystadenoma of the ovary. We report the second case in the literature of a MEST of the kidney along with a primary serous ovarian cystadenoma. We emphasize the hypothesis of the correlation between MESTs and hormonal milieu and the importance of clinical evaluation prior to the administration of any hormone therapy.